2015
DOI: 10.1111/ans.13396
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes after bariatric surgery in older patients: a state‐wide data‐linked cohort study

Abstract: Despite older age being associated with a higher risk of complications and longer hospital stays, there was a reduction in subsequent overall hospitalizations for older patients after bariatric surgery, suggesting that bariatric surgery may still confer health benefits to carefully selected obese older patients who cannot achieve weight loss by other means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The first published reports showed worse results of BS in older population (over 60-65 years old) compared with younger subjects, with lower weight loss outcomes and resolution of comorbidities, higher rate of complications, and post-operative mortality [23][24][25][26]. Nevertheless, more recent studies reported a tendency to better surgical outcomes in the elderly, probably due to better selection of patients and improvement of surgical techniques [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The first published reports showed worse results of BS in older population (over 60-65 years old) compared with younger subjects, with lower weight loss outcomes and resolution of comorbidities, higher rate of complications, and post-operative mortality [23][24][25][26]. Nevertheless, more recent studies reported a tendency to better surgical outcomes in the elderly, probably due to better selection of patients and improvement of surgical techniques [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…RYGB appears to be particularly effective at inducing weight loss in older adults compared to SG [36*]; however, older individuals undergoing RYGB have been noted to have an increased risk of nearly all perioperative complications associated with laparoscopic bariatric surgery and longer hospital stays [37]. Despite these findings, older bariatric patients still have a reduced rate of hospitalization following surgery and no difference in 30-day morality rates [38*].…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Dorman et al, 13 in a database analysis enrolling 48,378 individuals who underwent varied bariatric surgical techniques, observed that patients aged 65 years or older presented a non-statistically significant trend toward higher mortality and did not experience higher risk of major complications for either open or laparoscopic procedures; nonetheless, they were more likely to experience prolonged length of stay. Morgan and Ho, 14 in a retrospective cohort study enrolling 12,062 individuals who underwent bariatric surgery, observed that 18.1% of all the procedures were performed in patients ≥ 55 years old; older bariatric patients were statistically more likely to require longer hospital admissions, have more postoperative complications and require intensive care admissions compared to patients < 55 years old; however, 30-day (no deaths in the older cohort) and long-term mortality rates did not differ from those observed in younger individuals, suggesting that bariatric surgery may confer health benefits to carefully selected obese older patients who cannot achieve weight loss by other means. Batsis et al, 15 in a retrospective population-based study that analyzed 40 consecutive individuals aged 60 years or older who underwent bariatric surgery, observed a perioperative mortality of 2.5%, along with considerable weight loss, improvement in cardiovascular risk factors, and decrease in prevalence of metabolic syndrome, considering it to be an effective treatment in this population.…”
Section: Search Strategies Resultsmentioning
confidence: 99%